A day in the life of a firefighter - Hayward, Linda (London ; New York : DK, 2001)
Photographs and text follow firefighter Rob Green through a typical day at work, which includes the exciting rescue of a dog trapped in a house fire.
Includes index.
2.2
K-3
Keywords: Fire extinction -- Juvenile literature; Fire fighters; Fire extinction; Occupations; Fire fighters; Occupations